Meta-Analysis of Self-Efficacy and Anxiety Correlation - Zefanya Relita Trisnaningati (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Anxiety is a factor that almost everyone experiences. This makes anxiety an interesting topic to research. Various studies related to anxiety have been carried out. One of the factors believed to affect anxiety is self-efficacy. This study aims to strengthen statistically with a meta-analytic method regarding the relationship between self-efficacy and anxiety. This study involved 20 research journals on the correlation between Self-efficacy and Anxiety. The statistical test found that self-efficacy and anxiety had a low effect size correlation (r = -0.274958), with high heterogeneity (I² = 96.9%) and publication bias (E = 0.4603). Meta-analytic results show that self-efficacy does not play a significant role in anxiety.